New occurrence of the hygrobiotic mite family Homocaligidae (Acari, Raphignathoidea) in Turkey: Homocaligus crassipus Fan - Dogan, Salih; Dilkaraoglu, Sibel; Aksoy, Hakan; Aykut, Medeni; Fan, Qing-Hai (Systematic & Applied Acarology Soc London, Natural History Museum, 2014)
Most raphignathoid mites are characteristic of the drier edaphic microhabitats such as litter, soil, bark and moss. A few are fresh-water aquatic to sub-aquatic: species of the family Homocaligidae; and some species of Caligohomus Habeeb, 1966, Cheylostigmaeus Willmann, 1951 and Eustigmaeus Berlese, 1910 of the family Stigmaeidae. Homocaligidae has occasionally been reported from Asia, Australia, Europe, North America and South Africa. This rarely collected family has not been previously reported from Turkey, but now is known to be a part of the mite fauna of Turkey, with herein the re-description of Homocaligus crassipus Fan based on adults, protonymphs and deutonymphs found on hydrous grassy soil and moss wetland area, Eksisu Marsh, eastern part of Turkey. The male of H. crassipus is newly discovered and described here. Also, an identification key to the known species of the genus Homocaligus is presented.